ANALISIS KARAKTERISTIK SEDIMEN BERDASARKAN BUTIR SEDIMEN PADA KAWASAN SUNGAI SELOR ATAU SUNGAI BUAYA DI KABUPATEN BULUNGAN - Singal, Rachel Zandra; Maharani, Larasati Nur (Civil Engineering Scientific Journal, 2025)
ABSTRACT: Based on field observations, Sungai Buaya/Sungai Selor has a problem, namely sediment piles where the sediment piles are overgrown with water hyacinth and other aquatic plants, thus inhibiting the flow of river water. As a result, the river does not function properly. The formulation of the problem in this study is how are the characteristics of sediment grains in the waters of Sungai Selor/Sungai Buaya. The purpose of the study was to determine the size of sediment grains, the shape of sediment grains and the specific gravity of sediment grains in the waters of Sungai Selor/Sungai Buaya. The method used in this study was to take samples in the field by random sampling at 6 points in the location of Sungai Selor/Sungai Buaya. Sediment characteristic analysis was conducted in the laboratory, namely testing the size of sediment grains using the sieve analysis method in accordance with the ASTM D 422 standard, determining the shape of sediment grains using a microscope and testing the specific gravity of sediment based on SNI 1964: 2008. The results of the analysis showed that the type of sediment in the Selor River/Buaya River consisted of coarse sand with a grain size of 0.850 mm and medium sand with a size between 0.250 mm - 0.425 mm. The shape of sediment grains that dominate the waters of the Selor River or Buaya River is sub-angular with high sphericity, angular with medium sphericity; sub-rounded with medium sphericity; rounded with high sphericity; rounded with low sphericity. The specific gravity test that has been carried out obtained the results of the specific gravity of sediment in the Selor River/Buaya River between 2.128 - 2.609.Keywords: Sediment Characteristics, Sediment Grain Size, Sediment Form, Sediment Specific Gravity, Selor River/Buaya River. ABSTRAK: Berdasarkan pengamatan di lapangan bahwa Sungai Buaya/Sungai Selor memiliki permasalahan yaitu tumpukan sedimen dimana tumpukan sedimen itu ditumbuhi enceng gondok dan tanaman air lainnya,  sehingga menghambat aliran air sungai. Akibatnya sungai tidak berfungsi dengan baik. Rumusan masalah pada penelitian ini adalah bagaimana karakteristik butir sedimen pada perairan  Sungai Selor/Sungai Buaya. Tujuan penelitian adalah untuk mengetahui ukuran butir sedimen, bentuk butir sedimen dan berat jenis butir sedimen di perairan Sungai Selor/Sungai Buaya. Metode yang digunakan pada penelitian ini adalah dengan pengambilan sampel di lapangan dengan cara random sempling pada di 6 titik di lokasi Sungai Selor/Sungai Buaya. Analisa karakteristik sedimen dilakukan di laboratorium yaitu pengujian ukuran butir sedimen dengan menggunakan dengan metode analisa saringan yang sesuai dengan standar ASTM D 422, penentuan bentuk butir sedimen dilakukan menggunakan mikroskop dan pengujian berat jenis sedimen dilakukan berdasarkan SNI 1964 : 2008. Hasil analisa didapatkan jenis  sedimen di Sungai Selor/Sungai Buaya terdiri dari pasir kasar dengan ukuran butir 0,850 mm dan pasir sedang dengan ukuran antara 0,250 mm – 0,425 mm. Bentuk butir sedimen yang mendominasi perairan Sungai Selor atau Sungai Buaya adalah berbentuk menyudut tanggung dengan kebulatan tinggi (sub-angular with high sphericity berbentuk menyudut dengan kebulatan sedang (angular with medium sphericity); berbentuk membundar tanggung dengan kebulatan sedang (sub-rounded with medium sphericity); berbentuk membundar dengan kebulatan tinggi (rounded with high sphericity); berbentuk membundar dengan kebulatan rendah (rounded with low sphericity). Uji berat jenis yang telah dilakukan mendapatkan hasil berat jenis sedimen di Sungai Selor/Sungai Buaya antara 2.128 – 2,609.Kata kunci: Karakteristik Sedimen, Ukuran Butir Sedimen, Bentuk Sedimen, Berat Jenis Sedimen, Sungai Selor/Sungai Buaya